PUBLIC HEALTH EDUCATION THROUGH BLOOD PRESSURE, BLOOD SUGAR AND GOUT CHECKS IN PANGKEMIRI VILLAGE - Prasetyo, Ivan; Dwi, Mirta; Harsono, Budwi (Journal of Social Comunity Services, 2024)
General Background: Public health awareness, particularly in rural areas, is often limited, with people neglecting basic health monitoring. Specific Background: In Pangkemiri Village, health checks are rare, leading to undetected conditions related to blood pressure, blood sugar, and uric acid. Knowledge Gap: There is insufficient knowledge among the public regarding regular health checks and preventative care. Aims: This study aims to increase community awareness of health through free health checks and education organized by Real Work Lecture (KKN) students. Results: The activity involved blood pressure, blood sugar, and uric acid checks, as well as health education on maintaining normal levels. The high community participation demonstrated an increased understanding of health monitoring. Novelty: This initiative provided direct health services and consultations, empowering rural residents with critical information about their health status and prevention measures. Implications: The results indicate that continued health education and regular check-ups can lead to early detection of health conditions, fostering healthier lifestyles in the community. This program can serve as a model for future health-focused community service activities.